ANALISIS EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS DIGITAL TERHADAP MINAT BELAJAR DAN CAPAIAN AKADEMIK SISWA SEKOLAH DASAR - Rahma, Hafida; Indriana Eko Armaidi; Amin Yusuf; Edi Kurniawan; Ngabiyanto; Muh. Sholeh; Tri Joko Raharjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the effectiveness of digital-based learning media on learning interest and academic achievement among elementary school students in Indonesia. Using a systematic literature review and SWOT analysis, the research synthesizes data from studies published between 2020 and 2025. The results indicate that digital media, including gamification (Quizizz, Kahoot, Wordwall) and immersive technologies (Augmented Reality and Virtual Reality), significantly enhance student engagement and conceptual understanding. Statistical meta-analysis shows an effect size ranging from 1.07 to 2.49, which is considered highly significant in educational interventions. The integration of digital tools facilitates the visualization of abstract concepts, bridging the cognitive gap for students in the concrete operational stage. However, the success of digital implementation is heavily contingent upon teacher competency within the Technological Pedagogical Content Knowledge (TPACK) framework and the availability of infrastructure. This report provides a detailed abstract and a comprehensive conclusion as requested, emphasizing that joyful learning through digital media is a viable solution for post-pandemic education in Indonesia.